An Analysis Of Students’ Difficulties In Speaking English Through Conversation - Nurcahaya Citra Resmi Gulo; Feby Meuthia Yusuf; Yessy Marzona (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to analyze students' difficulties in speaking English through conversation at Ekasakti High School, Padang. Speaking is a very important language skill in supporting communication; however, many students still experience difficulties in expressing ideas orally in English. This study used a descriptive research design. The study population was all nine grade XI IPS students at Ekasakti High School, Padang, and all of them were used as a sample (total sampling). The research instrument was a speaking test in the form of an English conversation on the topic "Environmental Cleanliness". The assessment of students' speaking ability was based on five components: comprehension, grammar, vocabulary, pronunciation, and fluency. Data were analyzed using average scores and percentages. The results showed that the average score of students' speaking ability was 56.6%, which is categorized as moderate. The main difficulties faced by students were limited vocabulary, pronunciation errors, and anxiety when speaking.